Influence of Femoral Component Design on Retrograde Femoral Nail Starting Point. Issue 10 (October 2015) - Service, Benjamin C.; Kang, William; Turnbull, Nathan; Langford, Joshua; Haidukewych, George; Koval, Kenneth J.
Abstract : Purpose: Our experience with retrograde femoral nailing after periprosthetic distal femur fractures was that femoral components with deep trochlear grooves posteriorly displace the nail entry point resulting in recurvatum deformity. This study evaluated the influence of distal femoral prosthetic design on the starting point. Methods: One hundred lateral knee images were examined. The distal edge of Blumensaat's line was used to create a ratio of its location compared with the maximum anteroposterior condylar width called the starting point ratio (SPR). Femoral trials from 6 manufacturers were analyzed to determine the location of simulated nail position in the sagittal plane compared with the maximum anteroposterior prosthetic width. These measurements were used to create a ratio, the femoral component ratio (FCR). The FCR was compared with the SPR to determine if a femoral component would be at risk for retrograde nail starting point posterior to the Blumensaat's line. Results: The mean SPR was 0.392 ± 0.03, and the mean FCR was 0.416 ± 0.05, which was significantly greater ( P = 0.003). The mean FCR was 0.444 ± 0.06 for the cruciate retaining (CR) trials and was 0.393 ± 0.04 for the posterior stabilized trials; this difference was significant ( P < 0.001). Conclusions: The FCR for the femoral trials studied was significantly greater than the SPR for native knees and was significantly greater for CR femoral components compared with posterior stabilized components. These findings demonstrate that many total knee prostheses, particularly CR designs, are at risk for a starting point posterior to Blumensaat's line. Abstract : Supplemental Digital Content is Available in the Text.